PTPδ is a presynaptic organizer for the formation and maintenance of climbing fiber to Purkinje cell synapses in the developing cerebellum - Okuno, Yuto; Sakoori, Kazuto; Matsuyama, Kyoko; Yamasaki, Miwako; Watanabe, Masahiko; Hashimoto, Kouichi; Watanabe, Takaki; Kano, Masanobu (Frontiers in Molecular Neuroscience, 2023)
Functionally mature neural circuits are shaped during postnatal development by eliminating redundant synapses formed during the perinatal period. In the cerebellum of neonatal rodents, each Purkinje cell (PC) receives synaptic inputs from multiple (more than 4) climbing fibers (CFs). During the first 3 postnatal weeks, synaptic inputs from a single CF become markedly larger and those from the other CFs are eliminated in each PC, leading to mono-innervation of each PC by a strong CF in adulthood. While molecules involved in the strengthening and elimination of CF synapses during postnatal development are being elucidated, much less is known about the molecular mechanisms underlying CF synapse formation during the early postnatal period. Here, we show experimental evidence that suggests that a synapse organizer, PTPδ, is required for early postnatal CF synapse formation and the subsequent establishment of CF to PC synaptic wiring. We showed that PTPδ was localized at CF-PC synapses from postnatal day 0 (P0) irrespective of the expression of Aldolase C (Aldoc), a major marker of PC that distinguishes the cerebellar compartments. We found that the extension of a single strong CF along PC dendrites (CF translocation) was impaired in global PTPδ knockout (KO) mice from P12 to P29-31 predominantly in PCs that did not express Aldoc [Aldoc (–) PCs]. We also demonstrated via morphological and electrophysiological analyses that the number of CFs innervating individual PCs in PTPδ KO mice were fewer than in wild-type (WT) mice from P3 to P13 with a significant decrease in the strength of CF synaptic inputs in cerebellar anterior lobules where most PCs are Aldoc (–). Furthermore, CF-specific PTPδ-knockdown (KD) caused a reduction in the number of CFs innervating PCs with decreased CF synaptic inputs at P10-13 in anterior lobules. We found a mild impairment of motor performance in adult PTPδ KO mice. These results indicate that PTPδ acts as a presynaptic organizer for CF-PC formation and is required for normal CF-PC synaptic transmission, CF translocation, and presumably CF synapse maintenance predominantly in Aldoc (–) PCs. Furthermore, this study suggests that the impaired CF-PC synapse formation and development by the lack of PTPδ causes mild impairment of motor performance.